2015
DOI: 10.1007/s11682-015-9463-8
|View full text |Cite
|
Sign up to set email alerts
|

Increased spatial granularity of left brain activation and unique age/gender signatures: a 4D frequency domain approach to cerebral lateralization at rest

Abstract: Cerebral lateralization is a well-studied topic. However most of the research to date in functional magnetic resonance imaging (fMRI) has been carried out on hemodynamic fluctuations of voxels, networks, or regions of interest (ROIs). For example, cerebral differences can be revealed by comparing the temporal activation of an ROI in one hemisphere with the corresponding homotopic region in the other hemisphere. While this approach can reveal significant information about cerebral organization, it does not prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…Effects of diagnosis on the differences suggest that in these patients the differences are smaller, especially with connectivity involving cognitive control networks, which is consistent with a lack of lateralization in patients. Age and gender do not exhibit strong effects on the intra-hemisphere connectivity differences, which is consistent with our findings in 4D domain (Agcaoglu et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Effects of diagnosis on the differences suggest that in these patients the differences are smaller, especially with connectivity involving cognitive control networks, which is consistent with a lack of lateralization in patients. Age and gender do not exhibit strong effects on the intra-hemisphere connectivity differences, which is consistent with our findings in 4D domain (Agcaoglu et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Differences between cerebral hemispheres were first observed by Paul Broca (Broca, 1861) and Carl Wernicke (Wernicke, 1874). Since then, there have been numerous studies noting cerebral lateralization in healthy subjects based on homodynamic activation (Agcaoglu et al, 2014; Cai et al, 2013; Clements et al, 2006; Gobbele et al, 2008) in a 4D frequency domain framework applied to resting fMRI data (Agcaoglu et al, 2015) and using FC (Gee et al, 2011; Gotts et al, 2013; Liu et al, 2009; Nielsen et al, 2013; Stark et al, 2008; Zhu et al, 2014; Zuo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This allows rs-fMRI to be acquired from a wide range of populations including patient groups, participants with intellectual disabilities, pediatric groups, and even unconscious patients (Smitha et al, 2017). Since Biswal, Yetkin, Haughton, and Hyde (1995) initially observed that temporal correlation of low frequency fluctuations in rs-fMRI (<0.1 Hz) can provide an estimate of functional connectivity (FC), research on rs-fMRI has greatly increased (Agcaoglu et al, 2018;Agcaoglu, Miller, Mayer, Hugdahl, & Calhoun, 2016;Allen et al, 2011;Cetin et al, 2016;Haak, Marquand, & Beckmann, 2018;Hart et al, 2018;Park, Friston, Pae, Park, & Razi, 2018;Rashid et al, 2018;Smitha et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…An early but still cited model of interhemispheric cross-talk 23 proposed that the brain is a highly reciprocally interconnected neural network, characterized by a constantly shifting pattern of locally higher and lower activation levels. Studies using fMRI suggest that hemispherical interactions are characterized by both functional cooperation and competition [24][25][26] , and patterns of correlated brain activity at rest can be used to evaluate the extent of hemispheric asymmetry 27 . However, the exact functional mechanisms through which the hemispheres interact are still not well understood 27,28 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies using fMRI suggest that hemispherical interactions are characterized by both functional cooperation and competition [24][25][26] , and patterns of correlated brain activity at rest can be used to evaluate the extent of hemispheric asymmetry 27 . However, the exact functional mechanisms through which the hemispheres interact are still not well understood 27,28 . Here, we address two outstanding questions: to what extent are brain hemispheres engaged in a competitive behaviour in terms of nodal centrality?…”
Section: Introductionmentioning
confidence: 99%